American communalism and Indian secularism: religion and politics in India and the West - Archer, Robin (1999)
Much of the Indian debate on secularism is built around what seem to be the common sense assumptions about India and the west. But a close look at the impact of Protestant Puritanism on the relationship between religion and politics in the US suggests that these assumptions are mistaken. Far from having fundamentally different experiences, there are some striking similarities between India and the US: similarities which draw attention to potential long-term dangers for India. - Reproduced
Keywords: Secularism